2011
DOI: 10.1590/s0102-05362011000400012
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen levels in the cultivation of strawberries in soilless culture

Abstract: In soilless grown strawberry crops, the nitrogen concentration of the nutrient solution affects plant growth and fruit yield and quality. The present research was conducted to determine the effect of nitrogen concentration in the nutrient solution on plant growth and development and fruit yield and quality of this crop. Treatments consisted of five nutrient solutions at nitrogen concentrations of 6.5 (T1), 8.0 (T2), 9.5 (T3), 11.0 (T4) and 12.5 (T5) mmol L-1, in an entirely randomised experimental design with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…This effect is a consequence of an adequate supply of water and N to the crop through irrigation [16], which dilutes the accumulation of soluble solids into the fruit. Similar results were obtained by Andriolo et al [17], who found a decrease in soluble solids in treatments with high doses of nitrogen. Regarding the nutrient factor K + , an increase in the average weight of fruit, and consequently in yield, when high concentrations of K + were used was reported elsewhere [18,19]; in this sense, results showed the relevant role of K + as a main nutrient for an adequate yield [7,20].…”
Section: Plant Variablessupporting
confidence: 90%
“…This effect is a consequence of an adequate supply of water and N to the crop through irrigation [16], which dilutes the accumulation of soluble solids into the fruit. Similar results were obtained by Andriolo et al [17], who found a decrease in soluble solids in treatments with high doses of nitrogen. Regarding the nutrient factor K + , an increase in the average weight of fruit, and consequently in yield, when high concentrations of K + were used was reported elsewhere [18,19]; in this sense, results showed the relevant role of K + as a main nutrient for an adequate yield [7,20].…”
Section: Plant Variablessupporting
confidence: 90%
“…Due to the anoxic environment of the casts, bacterial populations are dominant, and the availability of the reduced form of nitrogen (NH 4 + ) is higher than oxidized forms (CHAPUIS-LARDY et al, 2010). Considering the high uptake of nitrogen by strawberry plants and the importance of this element in strawberry production, it is probable the increased availability of this nutrient is utilized for fruit production (ANDRIOLO et al, 2011), minimizing the effects of earthworms on the plant growth observed in other studies when compared with this experiment. Other mechanisms also can explain the positive effects of earthworms on plant productivity.…”
Section: Resultsmentioning
confidence: 75%
“…Neither yields nor fruit quality were significantly affected by the fertilizer levels which ranged 2.9–6.1 mmol L -1 for F1 and 5.8–12.2 mmol L -1 for F2 during the experiment ( Table 5 ). Similarly, fruit yield and firmness were not affected by an increase in nitrate concentration of the nutrient solution from 3.75 to 15 mmol L -1 [ 50 , 51 ]. The mean berry weights of 10.70–13.85 g ( Table 5 ) were similar to fruit caliber found with greenhouse-grown ‘Seascape in soilless culture [ 52 ].…”
Section: Resultsmentioning
confidence: 99%